Neobythitoides serratus, a new bathyal genus and species from the East China Sea (Teleostei, Ophidiidae) - Nielsen, Jørgen G.; Machida, Yoshihiko (Zootaxa, 2006)
A new genus and species of Ophidiidae is described on the basis of two specimens from the East China Sea. It is characterized by the following combination of characters: body slender, opercular spine strong, eye small (twice in snout), hind margin of preopercle serrated, two median basibranchial tooth patches with or without a pair of small circular tooth patches, sagitta large with undivided sulcus and 10–11 long rakers on anterior gill arch. It seems most similar to Neobythites, from which it can be separated by the small horizontal diameter of eye window 2.5–2.7 % SL vs. 3.7–6.0 % SL, the serrated hind margin of preopercle vs. preopercle with 0–3 spines and no serration, and a sagitta with undivided sulcus vs. divided sulcus.